OPPORTUNITIES FOR HUMAN RESOURCES DEVELOPMENT BY PROFESSIONAL INTEGRATION / REINTEGRATION - LAVINIA ELISABETA POPP (Annals of the University of Petrosani: Economics)
The present paper presents some opportunities for the development of human resources by means of professional insertion / reinsertion. It is about an intervention project, more precisely the establishment of a Centre for Career Counselling and Professional Requalification (CORP) within the University “Eftimie Murgu” of Reşita. The objective was the promotion of an inclusive society able to facilitate the access and integration on the labour market of the young unemployed. By its activities, the project forwards an inclusive model of social inclusion of the professionally inactive young people through individualised programmes of qualification - requalification, support and professional counselling. By its results the project contributed to the stimulation of the participation of young unemployed persons to the social, economic and educational life, the consideration of the importance of the role played by education and professional training among the youth.